POWER RELATIONS IN OPEN SOURCE SOFTWARE USE IN HIGHER EDUCATION LIBRARY IN BALI - Suhartika, I Putu; Haryanti, Ni Putu Premierita (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
This research focuses on the actors involved in using open source software. The interaction of these actors creates power relation among them. The power that arises is not only caused solely by position but also by knowledge possessed by these actors. This research uses the theory of the power relation of Foucault. The power relation theory from Foucault is used to analyze the things that happen behind the use of open source software. This study uses actors in the library as informants, such as the head of the library, users, IT staff, and others. The results showed that the background of open source software development is not merely aimed at technical matters, but also based on the ideology of the developer (programmer), the open source business model is very much determined by the community, besides this, power practice causes the power relations of actors who are equal and dominant, the sustainability of open source software in libraries, and the placement of knowledge as power in power relations